2023
DOI: 10.1039/d3sm01003a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the air–water surface mechanical behavior of water-spread block copolymer micelles

Daniel J. Fesenmeier,
Seyoung Kim,
You-Yeon Won

Abstract: In the pursuit of the development of a first-in-kind polymer lung surfactant (PLS) therapeutic, whose effects are biophysical in nature, a comprehensive understanding of the factors affecting the air-water surface...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A previous study found that the optical film thickness sharply increases when the monolayer transitions into collapse or wrinkle structure. 29 In the 50w sample, this elevation in t corresponded to the initiation of micelle film collapse at a specific Π of 61.6 mN/m and a corresponding A of 153.7 cm 2 . For the 60w and 70w samples, the rise in t took place at Π values of 58.4 and 54.9 mN/m and corresponding A values of 192.5 and 216.4 cm 2 , respectively, prior to the ultimate collapse regime.…”
Section: The Compressive Modulus (Ementioning
confidence: 90%
See 1 more Smart Citation
“…A previous study found that the optical film thickness sharply increases when the monolayer transitions into collapse or wrinkle structure. 29 In the 50w sample, this elevation in t corresponded to the initiation of micelle film collapse at a specific Π of 61.6 mN/m and a corresponding A of 153.7 cm 2 . For the 60w and 70w samples, the rise in t took place at Π values of 58.4 and 54.9 mN/m and corresponding A values of 192.5 and 216.4 cm 2 , respectively, prior to the ultimate collapse regime.…”
Section: The Compressive Modulus (Ementioning
confidence: 90%
“…A previous study found that the optical film thickness sharply increases when the monolayer transitions into collapse or wrinkle structure . In the 50w sample, this elevation in t corresponded to the initiation of micelle film collapse at a specific Π of 61.6 mN/m and a corresponding A of 153.7 cm 2 .…”
mentioning
confidence: 95%